2020
DOI: 10.1111/tid.13348
|View full text |Cite
|
Sign up to set email alerts
|

Case series of six kidney transplanted patients with COVID‐19 pneumonia treated with tocilizumab

Abstract: Severe acute respiratory syndrome coronavirus 2 (named SARS CoV-2/COVID-19) is a novel pandemic infectious disease, which emerged in Wuhan, China, in late December 2019 and spread rapidly worldwide. 1,2 At the time we are writing (05/10/2020), in Italy there are about 219 000 patients infected, 28 600 only in Piedmont, our region. 3 Clinically, the disease is characterized with fever, cough, dyspnea, diarrhea, and eventually respiratory failure. 4,5 According to their intrinsic frailty and comorbidities, trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…These trends are comparable to the demographics of the general KTx populations. 57 Many studies (31/37) reported the time from KTx to COVID-19 diagnosis 18,[21][22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][42][43][44][45][46][47][48][49][50][51][52][53] ; 77.4% of KTx recipients received their allograft more than 1 year before COVID-19 diagnosis (range 8 days-31 years). It is unclear whether this trend is simply a reflection of the patients with KTx or it disproportionally represents chronic transplant patients.…”
Section: F I G U R E 1 Distribution Of Published Articles Per Countrymentioning
confidence: 99%
See 1 more Smart Citation
“…These trends are comparable to the demographics of the general KTx populations. 57 Many studies (31/37) reported the time from KTx to COVID-19 diagnosis 18,[21][22][23][24][25][26][27][28][30][31][32][33][34][35][36][37][38][39][40][42][43][44][45][46][47][48][49][50][51][52][53] ; 77.4% of KTx recipients received their allograft more than 1 year before COVID-19 diagnosis (range 8 days-31 years). It is unclear whether this trend is simply a reflection of the patients with KTx or it disproportionally represents chronic transplant patients.…”
Section: F I G U R E 1 Distribution Of Published Articles Per Countrymentioning
confidence: 99%
“…Laboratory evaluation was included in 33 of 37 studies. 18,19,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][36][37][38][39][40][41][42][43][44]46,[48][49][50][51][52][53][54] Most patients presented with lymphopenia appears to be self-limited and its clinical implications are not well described in the literature. 60 Regarding radiographic findings in KTx COVID-19-infected patients, 78.5% presented with bilateral ground-glass opacities in both chest plain radiograph and CT scan of the chest.…”
Section: Symptomatology and Laboratory Findingsmentioning
confidence: 99%
“…The 2 patients who improved after tocilizumab treatment showed significant improvement in the lymphocyte count. 28 …”
Section: Discussionmentioning
confidence: 99%
“…At the point of study completion, median LOH and LOI was 14 days (range 11-34) and 8 days (range [5][6][7][8][9][10][11] in patients receiving tocilizumab, which was speci ed in 15 studies 10,[20][21][22][23]28,29,31,32,35,36,[38][39][40][41] and 8 studies 10,23,27,29,32,33,36,42 , separately. Moreover, the median duration of mechanical ventilation was 7 days (range 5-10) after treatment of tocilizumab which was documented in 9 articles 10,11,[21][22][23]27,28,40,41 ( Table 2).…”
Section: Impact Of Tocilizumab Treatment On Duration Of Hospitalizatimentioning
confidence: 99%